Undated engraving of Louis XIV of France with his wife (Marie Thérèse... - Auteur inconnu (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: Undated engraving of Louis XIV of France with his wife (Marie Thérèse of Austria) with their son, the Dauphin of France by an unknown artist.
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; Iconographie